TEACHERS UNDERSTANDING OF LEARNER AUTONOMY IN INDONESIAN CONTEXTS: FINDINGS FROM HIGH SCHOOLS AND THEIR IMPLICATIONS - Agustina, Dwi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
Learner autonomy has become one of the main topics in the current research and conferences in Indonesia. This suggests that learner autonomy has received more attention in Indonesian contexts. However, there has been no space for discussions about the meaning of learner autonomy from high school teachers points of view. A multi-case study conducted by Agustina (2017) has found diverse understanding of autonomy as reported by Junior High School English teachers in Magelang Regency, Central Java, Indonesia. This paper discusses those teachers understanding in a more detailed way along with the implications when the concept is understood differently. This paper supports Agustinas argument that the diversity in understanding and developing autonomy should be anticipated since teachers have different beliefs about autonomy. Referring to Agustinas findings this paper proposes the need to consider the consequences of allowing the presence of various understanding of learner autonomy particularly when it is set as an educational goal.